Progress in analytical approaches integrating Livestock and Biodiversity to identify HNV Montados - Pinto-Correia, Teresa (2016)
The World Congress Silvo-Pastoral Systems 2016 aims to gather researchers from different disciplines, practitioners and policy makers at different governance levels that deal with the management and sustainability of silvo-pastoral systems. In this way the congress will create a fertile context to progress through interdisciplinarity research approaches that can help translate scientific knowledge into new adaptive management solutions, and thus bridge from science to practice. The aim is also to gather and compare knowledge from silvo-pastoral systems around the world, which share drought as a limiting factor, so that they can be discussed and evaluated.